Guidelines to support HIV-affected individuals and couples to achieve pregnancy safely : update 2018 - Davies, Natasha E.C.G.; Ashford, Gail; Bekker, Linda-Gail; Chandiwana, Nomathemba; Cooper, Diane; Dyer, Silker J.; Jankelowitz, Lauren; Mhlongo, Otty; Mnyani, Coceka N.; Mulaudzi, Muhangwi B.; Moorhouse, Michelle; Myer, Landon; et al. (Southern African journal of HIV medicine, 2018)
In June 2011, the Southern African HIV Clinicians’ Society, together with an expert working group, developed the Guidelines on Safer Conception in Fertile HIV-Infected Individuals and Couples. Since then, interventions to manage and prevent HIV have evolved and, similarly, options for safer conception have expanded. These updated guidelines provide healthcare providers with up-to-date information to support efforts to optimise safer conception care.